Analysis of a Hybrid Unmanned Aerial Underwater Vehicle Considering the Environment Transition - Aoki, Vivian M.; Pinheiro, Pedro M.; Drews-Jr, Paulo L. J.; Cunha, Mauro A. B.; Tuchtenhagen, Lucas G. (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS); 2021: Anais do XIII Simpósio Brasileiro de Robótica e XVIII Simpósio Latino Americano de Robótica, 2021)
This work consists of understanding the dynamics of an autonomous vehicle that operates in both aerial and aquatic environments, also known as Hybrid Unmanned Aerial Underwater Vehicle (HUAUV). There is little research on operating a vehicle in more than one environment, and in the literature, aerial and underwater models are usually treated as separate systems. Aiming at taking into account the environment transition, this paper proposes a model for this transition. Studies of the significant effects for the transition zone such as drag forces, Coriolis effect, additional mass, and buoyancy force are carried out. The proposed transition model considers the density of the environment, which was identified as the parameter that most influences the dynamics. A variable density function is developed and added to the model, where it varies linearly between the densities of air and water as a function of height inside a boundary layer. Simulation results are presented to validate qualitatively the proposed model by comparing the behaviors of the vehicle with and without the transition model.